2001
DOI: 10.1073/pnas.071022298
|View full text |Cite
|
Sign up to set email alerts
|

RPN4 is a ligand, substrate, and transcriptional regulator of the 26S proteasome: A negative feedback circuit

Abstract: The RPN4 (SON1, UFD5) protein of the yeast Saccharomyces cerevisiae is required for normal levels of intracellular proteolysis. RPN4 is a transcriptional activator of genes encoding proteasomal subunits. Here we show that RPN4 is required for normal levels of these subunits. Further, we demonstrate that RPN4 is extremely short-lived (t 1/2 Ϸ2 min), that it directly interacts with RPN2, a subunit of the 26S proteasome, and that rpn4⌬ cells are perturbed in their cell cycle. The degradation signal of RPN4 was ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
401
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 414 publications
(416 citation statements)
references
References 55 publications
15
401
0
Order By: Relevance
“…The upregulation of the expression of some genes coding for proteasomal proteins, as a consequence of the inhibition of proteasome activity by both RNA interference and small molecules such as GM132, is a well-established phenomenon observed in several organisms including mammals (48)(49)(50)(51). Therefore, the data reported here, which show the ability of LLNle to inhibit the proteasome activity and concomitantly to upregulate the expression of genes coding for several proteasome subunits, are in line with these previous studies.…”
Section: Discussionsupporting
confidence: 92%
“…The upregulation of the expression of some genes coding for proteasomal proteins, as a consequence of the inhibition of proteasome activity by both RNA interference and small molecules such as GM132, is a well-established phenomenon observed in several organisms including mammals (48)(49)(50)(51). Therefore, the data reported here, which show the ability of LLNle to inhibit the proteasome activity and concomitantly to upregulate the expression of genes coding for several proteasome subunits, are in line with these previous studies.…”
Section: Discussionsupporting
confidence: 92%
“…2 These data support the argument of a possible common regulation of these subunits and, in addition, may also imply the existence of an autoregulatory mechanism. A common transcriptional regulation of the proteasomal subunits has been reported in yeast (51)(52)(53). 26 of the 32 proteasomal subunit genes have been found to be preceded in their promoters by proteasome-associated control element.…”
Section: Discussionmentioning
confidence: 84%
“…tpp2-1 plants were not hypersensitive to the 26S proteasome inhibitor MG132, nor were they hypersensitive to amino acid analogs, which, when incorporated into abnormal proteins, require the 26S proteasome for removal. Attenuated proteolysis generated by 26S proteasome mutations has been shown to coordinately enhance accumulation of both mRNA and protein for a battery of 26S proteasome subunits in yeast, animals, and Arabidopsis (Xie and Varshavsky, 2001;Meiners et al, 2003;Yang et al, 2004). Our data showed that a similar up-regulation does not occur upon loss of TPPII.…”
Section: Discussionmentioning
confidence: 99%